The sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
<h3>Sum of expressions</h3>
Expressions are equations separated by mathematical signs. This expressions are known to contains certain unknowns
Given the following expression
10x^2 +7x+6 and 6x + 5
We are to take the sum of both expression to have:
f(x) = 10x^2 +7x+6 + 6x + 5
Collect the like terms
f(x) = 10x^2 + 7x + 6x + 6 + 5
f(x) = 10x^2 + 13x + 11
Hence the sum of the given expression expressed as a quadratic equation is 10x^2 + 13x + 11
Learn more on sum of functions here: brainly.com/question/11602229
#SPJ1
Answer:
wut.
Step-by-step explanation:
Step-by-step explanation:
Equation of line is y-y1 = m(x-x1), where m is the slope and (x1,y1) is the given point.
y-2 = 1/4*(x-(-4))
y-2 = 1/4 * (x+4)
4*(y-2) = x+4
Equation of the line is,
x-4y = -12
90![\pi](https://tex.z-dn.net/?f=%5Cpi)
one revolution is the circumference of the circle.
C=
d=90![\pi](https://tex.z-dn.net/?f=%5Cpi)
Answer: B. (-2.5, 0.75)
<u>Step-by-step explanation:</u>
Use a graphing calculator or online graphing tool to graph the 2 equations.
The intersection of the two lines is the solution to the system.
The intersection is approximately at x = -2.5 and y = 0.75 <em>(See attachment) </em>